Enhancing Uterine Fibroid Care: Clinician Perspectives on Diagnosis, Disparities, and Strategies for Improving Health Care - Alfu Laily; Isha Nair; Sophie E. Shank; Cameron Wettschurack; Grace Khamis; Chandler Dykstra; Andrea L. DeMaria; Monica L. Kasting (Women's Health Reports)
Objective: To explore clinicians' perspectives on diagnosing, treating, and managing uterine fibroids, identifying gaps and challenges in health care delivery, and offering recommendations for improving care. Materials and Methods: A qualitative design was used to conduct 14 semistructured interviews with clinicians who treat fibroid patients in central Indiana. Interviews were audio recorded, transcribed verbatim, and analyzed using thematic analysis techniques. Constant comparative analysis was used to identify emergent themes. Results: Four themes emerged. (1) Lack of patient fibroid awareness: Patients lacked fibroid awareness, leading to challenges in explaining diagnoses and treatment. Misconceptions and emotional distress highlighted the need for better education. (2) Inequities in care and access: Health care disparities affected Black women and rural patients, with transportation, scheduling delays, and financial constraints hindering access. (3) Continuum of care: Clinicians prioritized patient-centered care and shared decision-making, tailoring treatment based on factors like severity, location, size, cost, fertility goals, and recovery time. (4) Coronavirus disease 2019 (COVID-19) impact: The pandemic posed challenges and opportunities, prompting telehealth adoption and consideration of nonsurgical options. Conclusions: Clinician perspectives noted patient challenges with fibroids, prompting calls for enhanced education, interdisciplinary collaboration, and accessible care to address crucial aspects of fibroid management and improve women's well-being. Practice Implications: Clinicians identified a lack of patient awareness and unequal access to fibroid care, highlighting the need for improved education and addressing disparities. Findings also emphasized the importance of considering multidimensional aspects of fibroid care and adapting to challenges posed by the COVID-19 pandemic, recommending broader education, affordability, interdisciplinary collaboration, and research for better fibroid health care.